(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This quantitative article analyzes how the use of virtual platforms (LMS such as Moodle, Canvas, and Blackboard; and synchronous tools such as Zoom and Microsoft Teams) relates to academic performance in university students. Based on a cross-sectional correlational design with n = 512 students from three faculties, we modeled the relationship between interactions in the LMS (logins, time on platform, participation in forums, punctual deliveries), attendance at video classes and self-regulation strategies with the weighted semester average. A multiple regression model showed that active participation in LMS (β = .31, p < .001) and self-regulation (β = .27, p < .001) predict performance, with indirect effects of video class attendance (β = .09, p = .021). The results dialogue with recent evidence linking learning analytics and SRLs with performance in higher education. We involve instructional design recommendations and ethical data analytics.